Spider silk-like microstructure shape memory polyimide composite material and preparation method and application thereof

By using the coupling design of intelligent polymer material and two-dimensional intercalation composite in shape memory polyimide composite, a spider-like silk microstructure is formed, and the flame retardant and electromagnetic shielding performance is improved through chemical grafting flame retardant and MXene intercalation composite, the problem of low electromagnetic shielding efficiency and insufficient flame retardant properties of composite materials is solved, and efficient electromagnetic shielding and flame retardant effects are achieved.

CN119529531AActive Publication Date: 2025-02-28HARBIN INST OF TECH +1

Patent Information

Application Number
CN202411790962.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Shape memory polyimide composites have low electromagnetic shielding performance and cannot take into account high flame retardancy.

Method used

The intelligent polymer material is coupled with the two-dimensional intercalation composite to form an organic-inorganic hybrid shape memory polyimide composite with a spider silk microstructure, and the flame retardant and electromagnetic shielding performance of the material is improved by chemical grafting flame retardant and MXene intercalation composite.

Benefits of technology

The shape memory polyimide composite material with high electromagnetic shielding performance and flame retardant properties has excellent mechanical and mechanical properties and shape memory properties, and is suitable for adaptive flexible thermal management electromagnetic shielding devices and smart wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005175300400000021
    Figure BDA0005175300400000021
  • Figure FDA0005175300390000011
    Figure FDA0005175300390000011
  • Figure HDA0005175300410000011
    Figure HDA0005175300410000011
Patent Text Reader

Abstract

The invention relates to a shape memory polyimide composite material with a spider-silk-like microstructure and a preparation method and application thereof. According to the method, the composite material is designed by coupling the spider-silk-like microstructure, shape memory polyimide, a flame retardant and an electromagnetic shielding two-dimensional intercalation compound. Conductive polyaniline and transition metal carbon / nitride are subjected to an intercalation reaction to prepare a Ti3C2Tx-coated PANI intercalation compound, then the Ti3C2Tx-coated PANI intercalation compound is compounded with SMPI to serve as a spider-silk-like microstructure to enhance the mechanical strength and electromagnetic shielding performance of a resin matrix, and when the thickness of the SMPI composite material is 100 micrometers, the electromagnetic shielding effectiveness of the SMPI composite material in the X wave band exceeds 25 dB, and 99% or above of incident microwaves are effectively shielded. In addition, the flame retardant grade of the composite material reaches V0 grade, the limit oxygen index is 39.1%, the composite material also has high temperature resistance and shape memory characteristics, the shape fixation rate is 96%, and the shape recovery rate is 97%. The composite material not only can eliminate electromagnetic interference, but also can resist flame, can be automatically deformed, and is applied to the fields of self-adaptive deformation thermal management electromagnetic shielding devices, intelligent wearable equipment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional polymers, and in particular relates to an organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardancy and electromagnetic shielding properties, and a preparation method and application thereof. Background Art

[0002] At present, electromagnetic wave pollution is considered to be the fourth largest pollution after air, water and noise pollution. High-density electromagnetic energy is radiated into the air, causing serious electromagnetic wave pollution, which not only endangers human health, but also endangers information security and the operating reliability of precision instruments. Traditional metal shielding materials have low density, poor flexibility, narrow absorption bandwidth and low chemical corrosion resistance, which to a certain extent limits their wide application; in addition, people's requirements for lightweight, portability and wearability of electronic products are gradually increasing. Therefore, in order to meet people's demand for advanced materials, it is urgent to find alternatives to traditional metal electromagnetic shielding materials. Conductive polymer composites (CPCs) have the advantages of good flexibility, good conductivity and easy processing, and have been recognized as the most promising electromagnetic shielding materials. Combining CPCs materials with smart materials and giving them intelligence is also a promising direction for the development of electromagnetic shielding materials in the future.

[0003] Shape memory polymer, referred to as SMP, is a smart material that actively changes shape under the stimulation of the external environment. Due to its light weight, low price, large deformation, and easy processing, it has broad application prospects in aerospace, space deployable structures, biomedical engineering, anti-counterfeiting engineering, soft robots and other fields. Shape memory polyimide (SMPI) has the advantages of high and low temperature resistance, good mechanical properties, flexibility, dimensional stability, corrosion resistance and radiation resistance, and has been widely favored by researchers. However, due to the high resistivity and low dielectric constant of SMPI, it needs to be modified to meet the application requirements of electromagnetic shielding. Transition metal carbon / nitrogen compound (MXene) is a two-dimensional nanomaterial composed of multiple elements, which is obtained by selectively etching the active metal elements in the MAX phase, among which Ti3C2T x It is the most widely studied one at present. Its surface contains abundant -OH, -O, and -F functional groups and has excellent electrical properties (conductivity is as high as 2.4×10 4 S / cm), optical properties and mechanical properties, and is widely used in batteries, sensors, supercapacitors, electromagnetic radiation protection, etc.

[0004] In summary, electromagnetic wave pollution not only endangers human health, but also endangers information security and the operating reliability of precision instruments. How to effectively protect against electromagnetic waves and protect equipment from electromagnetic radiation and interference is an urgent problem to be solved. In addition, electromagnetic shielding functional materials absorb electromagnetic waves and convert them into heat, causing the operating temperature of the equipment to increase. Therefore, protecting the equipment from fire hazards is also a problem that must be solved. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that the electromagnetic shielding effectiveness of shape memory polyimide composite materials is low and high flame retardancy cannot be taken into account, and to provide an organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardancy and electromagnetic shielding properties and its preparation method and application. The present invention uses intelligent polymer materials and two-dimensional intercalation composites to couple and design an organic-inorganic hybrid shape memory polyimide composite material with flame retardancy and electromagnetic shielding properties, forming a spider silk-like microstructure, giving the composite material excellent mechanical properties, which can be applied to adaptive flexible thermal management electromagnetic shielding devices and smart wearable devices in the future.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A spider silk-like microstructure shape memory polyimide composite material, the structural formula of the composite material is as follows:

[0008]

[0009] The value of n ranges from 100 to 165. In the chemical formula, the left side of the slash is the polymer matrix resin, and the right side is the particle, and the two form a composite material.

[0010] Furthermore, the composite material is composed of polyaniline and MXene intercalation composite (Ti3C2T x @PANI) and fluorine-containing, bromine-containing shape memory polyimide (SMPI); wherein the fluorine-containing, bromine-containing shape memory polyimide is synthesized from ternary monomers of 4,4'-diaminodiphenyl ether (ODA), hexafluoroisopropylphthalic anhydride (6FDA), and flame retardant 2,4,6-tribromoaniline (TBA), the total amount of 4,4'-diaminodiphenyl ether and 2,4,6-tribromoaniline and the amount of hexafluoroisopropylphthalic anhydride The ratio is 1:1-1.05, and the mass of 2,4,6-tribromoaniline accounts for 2wt%-10wt% of the mass of the fluorine-containing, bromine-containing shape memory polyimide.

[0011] The flame retardant 2,4,6-tribromoaniline (TBA) is chemically grafted into the molecular chain of shape memory polyimide to solve the shortcomings of easy precipitation and uneven filling of flame retardant physical filling. At the same time, 6FDA contains F element, which also has flame retardant function. The two can jointly improve the flame retardancy of SMPI. In addition, when the SMPI composite material burns, Ti3C2T x An oxidation reaction occurs in the air, and Ti-OH is gradually transformed into Ti-O-Ti by heat, and further reacts with oxygen and water to generate TiO2 and C. The generated TiO2 can form a physical protective layer on the MXene-SMPI interface, wrapping the residue produced after the carbonization of SMPI, effectively preventing the combustion of the material and the further spread of the flame, and improving the flame retardancy and fire resistance of the material.

[0012] Furthermore, the polyaniline and MXene intercalation composite (Ti3C2T x The mass ratio of @PANI) to fluorine-containing and bromine-containing shape memory polyimide is 5 to 20:100.

[0013] Furthermore, in the polyaniline and MXene intercalation composite, the mass percentage of polyaniline is 10%. x @PANI intercalation composites are used as electromagnetic shielding particles, in which the intercalation composites with lamellar wrinkled structures can be used as spider silk-like microstructures to improve the mechanical properties and electromagnetic shielding properties of the matrix SMPI, and enhance the interfacial bonding force between the particles and the resin.

[0014] A method for preparing the above-mentioned spider silk-mimicking microstructure shape memory polyimide composite material, the method comprising:

[0015] Step S1: Take a few or a single layer of Ti3C2T x The sample was dispersed in N, N-dimethylacetamide (DMAc) solvent, fully stirred at 40 °C for 48 h, and ultrasonically treated for 4 h. Then, polyaniline powder was weighed and added to the above DMAc solution and ultrasonicated for 4 h for intercalation reaction to obtain Ti3C2T x @PANI intercalation complex suspension;

[0016] Step S2, dissolving ODA and TBA in DMAc solvent to obtain a mixed solution containing -NH2 groups;

[0017] Step S3, adding 6FDA to the mixed solution containing -NH2 groups in 4-6 portions, reacting at room temperature for 20 hours under N2 atmosphere to obtain a polyamic acid solution, named PAA;

[0018] Step S4: Ti3C2T xPour the PAA solution into the PAA solution and stir evenly to obtain a suspension containing Ti3C2T x @PAA mixed solution of PANI intercalation complex;

[0019] Step S5, pouring the PAA mixed solution onto a substrate, placing it in a vacuum oven for vacuum drying to remove bubbles, and obtaining a PAA mixed solution substrate free of bubbles;

[0020] Step S6, placing the PAA mixed solution substrate without bubbles in a high-temperature oven, and performing thermal imidization by gradient heating to obtain a substrate containing a polyimide film;

[0021] Step S7, placing the substrate containing the polyimide film in water for 1-2 hours, completing demoulding, and after drying, obtaining an organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardancy and electromagnetic shielding properties.

[0022] Furthermore, in step S3, the concentration of polyamic acid in the polyamic acid solution is 17-24 wt %.

[0023] Furthermore, in step S5, the vacuum drying treatment includes: controlling the oven temperature to 50°C, maintaining it for 6 hours, then heating it to 80°C, maintaining it for 6 hours, and then evacuating the oven.

[0024] Further, in step S6, the gradient heating includes: heating to 140°C at a heating rate of 5°C / min, maintaining for 2 hours; heating to 200°C at a heating rate of 5°C / min, maintaining for 2 hours; heating to 260°C at a heating rate of 5°C / min, maintaining for 2 hours; heating to 300°C at a heating rate of 5°C / min, maintaining for 2 hours.

[0025] The spider silk-like microstructure shape memory polyimide composite material prepared by the above-mentioned preparation method is applied in cutting-edge technology fields such as advanced aircraft with adaptive active deformation, electronic appliances, thermal management electromagnetic shielding devices and smart wearable devices. For example: the adaptive thermal management electromagnetic shielding protective cover can protect the internal equipment from electromagnetic shielding interference. When the temperature of the equipment is too high and reaches the glass transition temperature of the SMPI composite material, the protective cover can actively deform and automatically open the preset heat dissipation path to reduce the temperature of the equipment and prevent fire hazards.

[0026] The beneficial effects of the present invention compared to the prior art are:

[0027] (1) The etched MXene surface is rich in -OH, -O, -F, and -Cl polar groups, which react with conductive polyaniline (PANI) to obtain Ti3C2T x@PANI intercalation composite, in which the layered wrinkled structure of Ti3C2T x It can be used as a spider silk-like microstructure to enhance the mechanical strength and toughness of the resin matrix and strengthen the interface bonding force between the resin and the resin.

[0028] (2) Ti3C2T x @PANI intercalation compound is compounded with polyamic acid, and after thermal imidization, a shape memory polyimide composite material with high electromagnetic shielding effectiveness and flame retardant properties is obtained, in which Ti3C2T x @PANI forms a strong hydrogen bond interaction with the imide groups in the SMPI matrix, giving MXene excellent dispersibility, compatibility with the matrix resin, and good mechanical properties and shape memory properties of the composite material. In the future, it can be applied to adaptive flexible thermal management electromagnetic shielding devices and smart wearable devices.

[0029] (3) The matrix resin and intercalation composite of the smart composite material also have a synergistic flame retardant effect. At the same time, the polyamic acid of the chemically grafted flame retardant 2,4,6-tribromoaniline and the F element in 6FDA make the polyimide obtained by thermal imidization have intrinsic flame retardant properties, solving the problems of precipitation and uneven dispersion of physical flame retardant particles. They can jointly improve the flame retardancy and fire resistance of SMPI and expand the application scope of smart materials in the field of high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a mechanism diagram of the shape memory effect of the polyimide composite material in an embodiment of the present invention;

[0031] Figure 2 Schematic diagram of spider silk-like microstructure and electromagnetic shielding mechanism of polyimide composite material in an embodiment of the present invention;

[0032] Figure 3 It is a flow chart of a method for preparing an organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material having flame retardancy and electromagnetic shielding properties in an embodiment of the present invention;

[0033] Figure 4 The synthetic route diagram of the organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardancy and electromagnetic shielding properties in the embodiment of the present invention;

[0034] Figure 5 The graph is a storage modulus and loss factor curve of the organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardancy and electromagnetic shielding properties in Example 1 of the present invention;

[0035] Figure 6The image and the measured limiting oxygen index diagram of the organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardancy and electromagnetic shielding properties in Example 1 of the present invention after a vertical combustion test;

[0036] Figure 7 This is a graph showing the electromagnetic shielding (EMI) performance of the organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardancy and electromagnetic shielding properties in Example 1 of the present invention in the frequency range of 8.2-12.4 GHz;

[0037] Figure 8 This is a diagram demonstrating the thermally driven shape memory process of the organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardancy and electromagnetic shielding properties in Example 1 of the present invention. DETAILED DESCRIPTION

[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.

[0039] It should be noted that, in the absence of conflict, the features in the embodiments of the present invention can be combined with each other. The meanings of the terms "comprise", "include", "contain", and "have" are non-restrictive, that is, other steps and other components that do not affect the results can be added. The above terms cover the terms "consisting of..." and "consisting essentially of...". Unless otherwise specified, materials, equipment, and reagents are all commercially available. At the same time, it should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the present invention described here can be implemented in an order other than those illustrated or described here.

[0040] The present invention intercalates and composites conductive polyaniline (PANI) with MXene to prepare Ti3C2T x @PANI intercalation composites, in which the intercalation composites with sheet-like wrinkles can be used as spider silk-like microstructures to enhance the interfacial bonding between the resin and the filler particles, making an important contribution to improving the mechanical properties and electromagnetic shielding properties of the composites. x The formation of strong hydrogen bonding interactions can give MXene excellent dispersibility and compatibility with the matrix resin. x@PANI intercalation composite is evenly mixed with polyamic acid solution of chemically grafted flame retardant 2,4,6-tribromoaniline, and after thermal imidization, an intelligent composite material with electromagnetic shielding effect, flame retardant effect and shape memory effect is obtained. It has broad application prospects in advanced aircraft with adaptive deformation, electronic appliances, thermal management electromagnetic shielding devices and smart wearable devices.

[0041] In principle, the polyimide of the present invention has a shape memory effect because its molecular chain segments form a fixed phase and a reversible phase in a physically cross-linked manner, wherein the fixed phase is a physical cross-linked network (i.e., a rigid chain) composed of π-π interactions, hydrogen bond interactions, and molecular chain entanglements between aromatic rings. The function of the fixed phase is to ensure that the molecular chain does not slide as a whole, thereby realizing a permanent shape memory function, while the reversible phase is an active phase (i.e., a flexible chain) that can undergo a reversible transformation, mainly composed of ether bond groups and -CF3 groups. Its shape memory transition is provided by a glass transition, and the molecular chain segments can be frozen under certain conditions and can be reactivated under external stimuli, thereby achieving temporary shape fixation and providing driving energy for shape recovery movement. When the temperature rises to T g When the temperature is above T (glass transition temperature), the microscopic Brownian motion of the molecular chain segments of the reversible phase intensifies, while the stationary phase is still in a solidified state. At this time, a certain external force is applied to cause the polymer to deform. By maintaining this external force to lower the temperature, the motion of the molecular chain segments of the reversible phase is "frozen" and a temporary shape is obtained. When the temperature is raised to T again, the reversible phase will be deformed. g When the temperature is above 5000 °C, the reversible phase softens, the stationary phase remains solidified, the molecular chain segments of the reversible phase "thaw" and gradually reach a thermodynamic equilibrium state under the action of the recovery stress of the stationary phase, which manifests itself as a recovery shape from a macroscopic perspective.

[0042] The electromagnetic shielding mechanism is as follows: Transition metal carbon / nitrogen compound (MXene) is a two-dimensional nanomaterial composed of multiple elements, which is obtained by selectively etching the active metal elements in the MAX phase. x At present, the most extensive research has excellent electrical properties. At the same time, polyaniline is a conductive polymer material. The intercalation composite Ti3C2T x @PANI also has good electrical conductivity. The incident electromagnetic wave is x @PANI / SMPI composite material surface material-air impedance mismatch produces a certain reflection loss, and the electromagnetic waves entering the material and the high charge density Ti3C2T x @PANI interacts with each other, attenuates inside the material and generates conductive losses. At the same time, the special spider silk-like microstructure is also conducive to multiple reflections of electromagnetic waves inside the material, further enhancing its electromagnetic wave dissipation capacity. In addition, Ti3C2T xThe asymmetric charge distribution at the interface of @PANI and SMPI as well as the defects and terminal functional groups of MXene also lead to interfacial and dipole polarization losses of the incident electromagnetic waves. Therefore, both the reflection and absorption of electromagnetic waves contribute to the excellent electromagnetic shielding performance.

[0043] The flame retardant mechanism is as follows: the synergistic effect between MXene and SMPI makes the SMPI composite film have good flame retardant properties. After MXene is burned, an oxidation reaction occurs in the air, and Ti-OH is gradually heated to Ti-O-Ti, and further reacts with oxygen and water to generate TiO2 and C. The generated TiO2 can form a physical protective layer on the MXene-SMPI interface, wrapping the residue produced after SMPI carbonization, effectively preventing the material from burning and further propagation of the flame. In addition, the monomer 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 4,4'-diaminodiphenyl ether and 2,4,6-tribromoaniline ternary monomers are selected to synthesize the intrinsic flame retardant shape memory polyimide. The flame retardant 2,4,6-tribromoaniline in the SMPI is chemically grafted into the SMPI molecular chain segment, and 6FDA contains F elements. Br and F elements work together to play a synergistic flame retardant function, which protects the equipment from fire hazards, thereby improving the safety of SMPI. The present invention is further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0044] Example 1

[0045] (1) Take 0.2449 g of a few or single-layer Ti3C2T x The sample was dispersed in 12 mL of N, N-dimethylacetamide (DMAc) solvent, stirred at 40 °C for 48 h, and ultrasonicated for 4 h. Then 0.0245 g of polyaniline powder was added to the DMAc solution and ultrasonicated for 4 h for intercalation reaction to obtain Ti3C2T x @PANI intercalation complex suspension;

[0046] (2) 4.8 mmol ODA and 0.4 mmol TBA were dissolved in 16 mL DMAc solvent to obtain a mixed solution containing -NH2 groups;

[0047] (3) adding 5 mmol 6FDA to the mixed solution containing -NH2 groups in 4-6 portions, reacting at room temperature for 20 h under N2 atmosphere to obtain a polyamic acid solution, named PAA;

[0048] (4) Ti3C2T x The PAA solution was poured into the PAA solution and stirred at a speed of 500 r / min for 2 h to obtain a Ti3C2T x@PAA mixed solution of PANI intercalation complex;

[0049] (5) pouring the PAA mixed solution onto a substrate, placing it in a vacuum oven at 50° C. for 6 h; 80° C. for 6 h, evacuating the air to remove bubbles, and obtaining a PAA mixed solution substrate free of bubbles;

[0050] (6) placing the bubble-free PAA mixed solution substrate in a high-temperature oven and performing thermal imidization by gradient heating, with a heating rate of 5°C / min, heating to 140°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 200°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 260°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 300°C, and maintaining for 2 hours;

[0051] (7) Turn off the high-temperature oven, cool naturally to room temperature, take out the glass plate, and place it in deionized water at 100° C. for 1 h to complete demolding;

[0052] (8) The film material after demolding is placed in an oven at 100° C. for 6 hours to evaporate the water, thereby obtaining an organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardant and electromagnetic shielding properties.

[0053] in, Figure 5 is a storage modulus and loss factor curve of the polyimide composite material prepared in this embodiment; Figure 6 The image and the measured limiting oxygen index of the polyimide composite material prepared in this embodiment after the vertical combustion test; Figure 7 The electromagnetic shielding (EMI) performance of the polyimide composite material prepared in this embodiment in the frequency range of 8.2-12.4 GHz; Figure 8 This is a diagram demonstrating the heat-driven shape memory process of the polyimide composite material prepared in this embodiment.

[0054] from Figure 5 It can be seen that the T g The shape memory transition temperature is 320℃, and the storage modulus is 9192MPa at room temperature. Figure 6 It can be seen that the polyimide composite material prepared in this embodiment burns vertically without flame extension, extinguishes itself when away from the fire, has no molten droplets, and cannot ignite the absorbent cotton. The surface of the material turns black after burning, and white attachments are generated on the surface. The flame retardant grade reaches UL94 VTM-0, and the limiting oxygen index is 39.1%. Compared with pure polyimide without intercalation composites, the limiting oxygen index is increased by 9.7%. Figure 7It can be seen that the total electromagnetic shielding (EMI) efficiency of the polyimide composite material prepared in this embodiment is 28.4 dB in the frequency range of 8.2-12.4 GHz, which can meet the requirements of commercial-grade EMI shielding applications and effectively shield more than 99% of incident microwaves. Figure 8 It can be seen that the polyimide composite material prepared in this embodiment is subjected to external force to shape the polyimide in a 340°C thermal environment, and the temperature is lowered to room temperature. After the external force is removed, the temporary curved shape is still maintained. When heated to a 340°C thermal environment again, the original shape can be restored after 15 seconds, wherein the shape fixation rate is 96% and the shape recovery rate is 97%.

[0055] Example 2

[0056] (1) Take 0.3314 g of a few or single-layer Ti3C2T x The sample was dispersed in 12 mL of N, N-dimethylacetamide (DMAc) solvent, stirred at 40 °C for 48 h, and ultrasonicated for 4 h. Then 0.0301 g of polyaniline powder was added to the DMAc solution and ultrasonicated for 4 h for intercalation reaction to obtain Ti3C2T x @PANI intercalation complex suspension;

[0057] (2) 4.8 mmol ODA and 0.4 mmol TBA were dissolved in 16 mL DMAc solvent to obtain a mixed solution containing -NH2 groups;

[0058] (3) adding 5.01 mmol 6FDA to the mixed solution containing -NH2 groups in 4-6 portions, reacting at room temperature for 20 h under N2 atmosphere to obtain a polyamic acid solution, named PAA;

[0059] (4) Ti3C2T x The PAA solution was poured into the PAA solution and stirred at a speed of 500 r / min for 2 h to obtain a Ti3C2T x @PAA mixed solution of PANI intercalation complex;

[0060] (5) pouring the PAA mixed solution onto a substrate, placing it in a vacuum oven at 50° C. for 6 h; 80° C. for 6 h, evacuating the air to remove bubbles, and obtaining a PAA mixed solution substrate free of bubbles;

[0061] (6) placing the bubble-free PAA mixed solution substrate in a high-temperature oven and performing thermal imidization by gradient heating, with a heating rate of 5°C / min, heating to 140°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 200°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 260°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 300°C, and maintaining for 2 hours;

[0062] (7) Turn off the high-temperature oven, cool naturally to room temperature, take out the glass plate, and place it in deionized water at 100° C. for 1 h to complete demolding;

[0063] (8) The film material after demolding is placed in an oven at 100° C. for 6 hours to evaporate the water, thereby obtaining an organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardant and electromagnetic shielding properties.

[0064] The T of the polyimide composite material prepared in this embodiment is g The shape memory transition temperature is 323°C, that is, the storage modulus is 9252MPa at room temperature; the flame retardant grade reaches UL94 VTM-0, and the limiting oxygen index is 39.5%; the total electromagnetic shielding (EMI) efficiency in the frequency range of 8.2-12.4GHz is 28.5dB; the shape fixation rate is 95%, and the shape recovery rate is 97%.

[0065] Example 3

[0066] (1) Take 0.2336 g of a few or single-layer Ti3C2T x The sample was dispersed in 12 mL of N, N-dimethylacetamide (DMAc) solvent, stirred at 40 °C for 48 h, and ultrasonicated for 4 h. Then 0.0234 g of polyaniline powder was added to the DMAc solution and ultrasonicated for 4 h for intercalation reaction to obtain Ti3C2T x @PANI intercalation complex suspension;

[0067] (2) 4.8 mmol ODA and 0.4 mmol TBA were dissolved in 16 mL DMAc solvent to obtain a mixed solution containing -NH2 groups;

[0068] (3) adding 5.05 mmol 6FDA to the mixed solution containing -NH2 groups in 4-6 portions, reacting at room temperature for 20 h under N2 atmosphere to obtain a polyamic acid solution, named PAA;

[0069] (4) Ti3C2T x The PAA solution was poured into the PAA solution and stirred at a speed of 500 r / min for 2 h to obtain a Ti3C2Tx @PAA mixed solution of PANI intercalation complex;

[0070] (5) pouring the PAA mixed solution onto a substrate, placing it in a vacuum oven at 50° C. for 6 h; 80° C. for 6 h, evacuating the air to remove bubbles, and obtaining a PAA mixed solution substrate free of bubbles;

[0071] (6) placing the bubble-free PAA mixed solution substrate in a high-temperature oven and performing thermal imidization by gradient heating, with a heating rate of 5°C / min, heating to 140°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 200°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 260°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 300°C, and maintaining for 2 hours;

[0072] (7) Turn off the high-temperature oven, cool naturally to room temperature, take out the glass plate, and place it in deionized water at 100° C. for 1 h to complete demolding;

[0073] (8) The film material after demolding is placed in an oven at 100° C. for 6 hours to evaporate the water, thereby obtaining an organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardant and electromagnetic shielding properties.

[0074] The T of the polyimide composite material prepared in this embodiment is g The shape memory transition temperature is 317°C, that is, the storage modulus is 8832MPa at room temperature; the flame retardant grade reaches UL94 VTM-0, and the limiting oxygen index is 36.9%; the total electromagnetic shielding (EMI) efficiency in the frequency range of 8.2-12.4GHz is 25.5dB; the shape fixation rate is 97%, and the shape recovery rate is 99%.

[0075] Example 4

[0076] (1) Take 0.4898 g of a few or single-layer Ti3C2T x The sample was dispersed in 24 mL of N, N-dimethylacetamide (DMAc) solvent, stirred at 40 °C for 48 h, and ultrasonicated for 4 h. Then 0.0490 g of polyaniline powder was added to the DMAc solution and ultrasonicated for 4 h for intercalation reaction to obtain Ti3C2T x @PANI intercalation complex suspension;

[0077] (2) 8.2 mmol ODA and 0.8 mmol TBA were dissolved in 32 mL DMAc solvent to obtain a mixed solution containing -NH2 groups;

[0078] (3) adding 8.6 mmol 6FDA to the mixed solution containing -NH2 groups in 4-6 portions, reacting at room temperature for 20 h under N2 atmosphere to obtain a polyamic acid solution, named PAA;

[0079] (4) Ti3C2T x The PAA solution was poured into the PAA solution and stirred at a speed of 500 r / min for 2 h to obtain a Ti3C2T x @PAA mixed solution of PANI intercalation complex;

[0080] (5) pouring the PAA mixed solution onto a substrate, placing it in a vacuum oven at 50° C. for 6 h; 80° C. for 6 h, evacuating the air to remove bubbles, and obtaining a PAA mixed solution substrate free of bubbles;

[0081] (6) placing the bubble-free PAA mixed solution substrate in a high-temperature oven and performing thermal imidization by gradient heating, with a heating rate of 5°C / min, heating to 140°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 200°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 260°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 300°C, and maintaining for 2 hours;

[0082] (7) Turn off the high-temperature oven, cool naturally to room temperature, take out the glass plate, and place it in deionized water at 100° C. for 1 h to complete demolding;

[0083] (8) The film material after demolding is placed in an oven at 100° C. for 6 hours to evaporate the water, thereby obtaining an organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardant and electromagnetic shielding properties.

[0084] The T of the polyimide composite material prepared in this embodiment is g The shape memory transition temperature is 318°C, that is, the storage modulus is 9200MPa at room temperature; the flame retardancy grade reaches UL94 VTM-0, and the limiting oxygen index is 38.7%; the total electromagnetic shielding (EMI) efficiency in the frequency range of 8.2-12.4GHz is 27.5dB; the shape fixation rate is 95%, and the shape recovery rate is 95%.

[0085] Example 5

[0086] (1) Take 0.4898 g of a few or single-layer Ti3C2T xThe sample was dispersed in 24 mL of N, N-dimethylacetamide (DMAc) solvent, fully stirred at 40 °C for 48 h, and ultrasonically treated for 4 h. Then, 0.0490 g of polyaniline powder was weighed and added to the above DMAc solution and ultrasonically treated for 4 h for intercalation reaction to obtain a Ti3C2Tx@PANI intercalation composite suspension.

[0087] (2) 8.2 mmol ODA and 0.8 mmol TBA were dissolved in 32 mL DMAc solvent to obtain a mixed solution containing -NH2 groups;

[0088] (3) adding 8.64 mmol 6FDA to the mixed solution containing -NH2 groups in 4-6 portions, reacting at room temperature for 20 h under N2 atmosphere to obtain a polyamic acid solution, named PAA;

[0089] (4) Ti3C2T x The PAA solution was poured into the PAA solution and stirred at a speed of 500 r / min for 2 h to obtain a Ti3C2T x @PAA mixed solution of PANI intercalation complex;

[0090] (5) pouring the PAA mixed solution onto a substrate, placing it in a vacuum oven at 50° C. for 6 h; 80° C. for 6 h, evacuating the air to remove bubbles, and obtaining a PAA mixed solution substrate free of bubbles;

[0091] (6) placing the bubble-free PAA mixed solution substrate in a high-temperature oven and performing thermal imidization by gradient heating, with a heating rate of 5°C / min, heating to 140°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 200°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 260°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 300°C, and maintaining for 2 hours;

[0092] (7) Turn off the high-temperature oven, cool naturally to room temperature, take out the glass plate, and place it in deionized water at 100° C. for 1 h to complete demolding;

[0093] (8) The film material after demolding is placed in an oven at 100° C. for 6 hours to evaporate the water, thereby obtaining an organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardant and electromagnetic shielding properties.

[0094] The T of the polyimide composite material prepared in this embodiment is gThe shape memory transition temperature is 321°C, that is, the storage modulus is 9176MPa at room temperature; the flame retardant grade reaches UL94 VTM-0, and the limiting oxygen index is 38.9%; the total electromagnetic shielding (EMI) efficiency in the frequency range of 8.2-12.4GHz is 28.2dB; the shape fixation rate is 98%, and the shape recovery rate is 95%.

[0095] Example 6

[0096] (1) Take 0.4858 g of a few or single-layer Ti3C2T x The sample was dispersed in 24 mL of N, N-dimethylacetamide (DMAc) solvent, stirred at 40 °C for 48 h, and ultrasonicated for 4 h. Then 0.0486 g of polyaniline powder was added to the DMAc solution and ultrasonicated for 4 h for intercalation reaction to obtain Ti3C2T x @PANI intercalation complex suspension;

[0097] (2) 8.2 mmol ODA and 0.8 mmol TBA were dissolved in 32 mL DMAc solvent to obtain a mixed solution containing -NH2 groups;

[0098] (3) adding 8.62 mmol 6FDA to the mixed solution containing -NH2 groups in 4-6 portions, reacting at room temperature for 20 h under N2 atmosphere to obtain a polyamic acid solution, named PAA;

[0099] (4) Ti3C2T x The PAA solution was poured into the PAA solution and stirred at a speed of 500 r / min for 2 h to obtain a Ti3C2T x @PAA mixed solution of PANI intercalation complex;

[0100] (5) pouring the PAA mixed solution onto a substrate, placing it in a vacuum oven at 50° C. for 6 h; 80° C. for 6 h, evacuating the air to remove bubbles, and obtaining a PAA mixed solution substrate free of bubbles;

[0101] (6) placing the bubble-free PAA mixed solution substrate in a high-temperature oven and performing thermal imidization by gradient heating, with a heating rate of 5°C / min, heating to 140°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 200°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 260°C, and maintaining for 2 hours; a heating rate of 5°C / min, heating to 300°C, and maintaining for 2 hours;

[0102] (7) Turn off the high-temperature oven, cool naturally to room temperature, take out the glass plate, and place it in deionized water at 100° C. for 1 h to complete demolding;

[0103] (8) The film material after demolding is placed in an oven at 100° C. for 6 hours to evaporate the water, thereby obtaining an organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardant and electromagnetic shielding properties.

[0104] The T of the polyimide composite material prepared in this embodiment is g The shape memory transition temperature is 322°C, that is, the storage modulus is 9158MPa at room temperature; the flame retardant grade reaches UL94 VTM-0, and the limiting oxygen index is 37.3%; the total electromagnetic shielding (EMI) efficiency in the frequency range of 8.2-12.4GHz is 26.9dB; the shape fixation rate is 94%, and the shape recovery rate is 97%.

[0105] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A spider silk-like microstructure shape memory polyimide composite material, characterized in that: The structural formula of the composite material is shown below: The value range of n is 100-165.

2. The spider silk-like microstructure shape memory polyimide composite material according to claim 1, characterized in that: The composite material is prepared from a polyaniline and MXene intercalation composite and a fluorine-containing and bromine-containing shape memory polyimide; wherein the fluorine-containing and bromine-containing shape memory polyimide is synthesized from ternary monomers of 4,4'-diaminodiphenyl ether, hexafluoroisopropylphthalic anhydride and 2,4,6-tribromoaniline, the total amount of 4,4'-diaminodiphenyl ether and 2,4,6-tribromoaniline and the amount of hexafluoroisopropylphthalic anhydride are in a ratio of 1:1-1.05, and the mass of 2,4,6-tribromoaniline accounts for 2wt%-10wt% of the mass of the fluorine-containing and bromine-containing shape memory polyimide.

3. The spider silk-like microstructure shape memory polyimide composite material according to claim 2, characterized in that: The mass ratio of the polyaniline and MXene intercalation composite to the fluorine-containing and bromine-containing shape memory polyimide is 5 to 20:

100.

4. The spider silk-like microstructure shape memory polyimide composite material according to claim 2 or 3, characterized in that: In the polyaniline and MXene intercalation composite, the mass percentage of polyaniline is 10%.

5. A method for preparing a spider silk-like microstructure shape memory polyimide composite material according to any one of claims 1 to 4, characterized in that: The method is: Step S1: Take a few or a single layer of Ti3C2T x The sample was dispersed in N, N-dimethylacetamide (DMAc) solvent, fully stirred at 40 °C for 48 h, and ultrasonically treated for 4 h. Then, polyaniline powder was weighed and added to the above DMAc solution and ultrasonicated for 4 h for intercalation reaction to obtain Ti3C2T x @PANI intercalation complex suspension; Step S2, dissolving ODA and TBA in DMAc solvent to obtain a mixed solution containing -NH2 groups; Step S3, adding 6FDA to the mixed solution containing -NH2 groups in 4-6 portions, reacting at room temperature for 20 hours under N2 atmosphere to obtain a polyamic acid solution, named PAA; Step S4: Ti3C2T x Pour the PAA solution into the PAA solution and stir evenly to obtain a suspension containing Ti3C2T x @PAA mixed solution of PANI intercalation complex; Step S5, pouring the PAA mixed solution onto a substrate, placing it in a vacuum oven for vacuum drying to remove bubbles, and obtaining a PAA mixed solution substrate free of bubbles; Step S6, placing the PAA mixed solution substrate without bubbles in a high-temperature oven, and performing thermal imidization by gradient heating to obtain a substrate containing a polyimide film; Step S7, placing the substrate containing the polyimide film in water for 1-2 hours, completing demoulding, and after drying, obtaining an organic-inorganic hybrid spider silk-like microstructure shape memory polyimide composite material with flame retardancy and electromagnetic shielding properties.

6. The method for preparing a spider silk-like microstructure shape memory polyimide composite material according to claim 5, characterized in that: In step S3, the concentration of polyamic acid in the polyamic acid solution is 17-24 wt %.

7. The method for preparing a spider silk-like microstructure shape memory polyimide composite material according to claim 5, characterized in that: In step S5, the vacuum drying treatment includes: controlling the oven temperature to 50°C, maintaining it for 6 hours, then heating it to 80°C, maintaining it for 6 hours, and then evacuating it.

8. The method for preparing a spider silk-like microstructure shape memory polyimide composite material according to claim 5, characterized in that: In step S6, the gradient heating includes: heating to 140°C at a heating rate of 5°C / min, maintaining for 2 hours; heating to 200°C at a heating rate of 5°C / min, maintaining for 2 hours; heating to 260°C at a heating rate of 5°C / min, maintaining for 2 hours; heating to 300°C at a heating rate of 5°C / min, maintaining for 2 hours.

9. Application of a spider silk-like microstructure shape memory polyimide composite material prepared by the preparation method according to any one of claims 5 to 8 in advanced aircraft with adaptive deformation, electronic appliances, thermal management electromagnetic shielding devices and smart wearable devices.

Citation Information

Patent Citations

  • High-temperature-resistant thermoplastic shape memory polyimide and preparation method thereof

    CN103980492A

  • Flexible polyimide-based composite dielectric film material and preparation method and application thereof

    CN110330646A

  • Preparation method of Co3O4 / PANI / MXene / PI electromagnetic shielding fabric

    CN110846881A

  • MXene polyimide composite film and preparation method thereof

    CN115819810A

  • Flame-retardant resin composition

    JP1993105725A

Cited By

  • High-strength BOPA film and preparation method thereof

    CN119912808A

  • Electromagnetic shielding flame-retardant fabric and preparation method thereof

    CN120537118A